Decrease in serum calcitriol (but not free 25-hydroxyvitamin D) concentration in hip fracture healing - Vaculik, J; Wenchich, L; Bobelyak, M; Pavelka, K; Stepan, J J (Journal of endocrinological investigation, 2021)
OBJECTIVE: To assess the decrease in serum calcitriol concentrations after hip fracture. METHODS: Serum concentrations of calcitriol, 25(OH)D, parathyroid hormone (PTH), directly measured free 25(OH)D, and indices of bone formation were measured in elderly patients with hip fracture (HF) and patients with elective hip replacement (EHR) at admission and after 7 weeks. RESULTS: A total of 45 patients with HF and 17 patients with EHR completed this prospective study. Baseline serum calcitriol levels were ≤ 60 pmol/l in 26% of the HF patients. After 7 weeks, they significantly decreased (p < 0.001). In patients with EHR, serum calcitriol was within the reference range in all but one patient and did not change during the 7-week recovery phase. Seven weeks after HF, a significant positive relationship was observed between the change in calcitriol and serum 25(OH)D concentration (r = 0.385, p = 0.009) and free 25(OH)D (r = 0.296, p = 0.048), and a decrease in calcitriol during recovery was associated with a decrease in serum PTH (p = 0.038). Seven weeks after HF, changes in both serum PTH and serum 25(OH)D concentrations contributed to the prediction of changes in serum calcitriol (R2 = 0.190, p = 0.012). CONCLUSIONS: Unlike patients with EHR, subjects with HF had low serum 25(OH)D and low free 25(OH)D concentrations at admission, while their serum 1,25D levels were relatively elevated. Decreases in circulating calcitriol levels in the 7 weeks following hip surgery were associated with a resolution of secondary hyperparathyroidism and low availability of free 25(OH)D.
Keywords: prospektivní studie; Hip Fractures; náhrada kyčelního kloubu; Calcitriol; senioři nad 80 let; Reference Values; Fracture Healing; Humans; lidé; Vitamin D; osteogeneze; kalcitriol; vitamin D; Free 25 hydroxyvitamin D; Parathyroid Hormone; Aged, 80 and over; Arthroplasty, Replacement, Hip; Female; Male; Prospective Studies; Osteogenesis; referenční hodnoty; mužské pohlaví; Fracture healing; Total 25 hydroxyvitamin D; Aged; fraktury kyčle; Hip fracture; ženské pohlaví; hojení fraktur; parathormon; senioři